SEDIMENTOLOGI DAN AKUMULASI KASITERIT PADA ENDAPAN ALUVIUM SEPANJANG AIR INAS HINGGA LAUT LEPAS PANTAI TANJUNG KUBU (TOBOALI), BANGKA SELATAN - Herman Moechtar; S. Hidayat (Jurnal Geologi dan Sumberdaya Mineral, 2010)
Placer cassiterite deposits of Air Inas suggest that the deposits consist of mass flows of coarse grains (A1), mass flows of fine grains (A2), offshores (B.1), nearshores (B2), fluvial (B3), Recent deposits of nearshores (C1), and flood basin deposits (C2). The research was based on analizing sedimentology and stratigraphy of eleven boreholes available along North to South traverse. Depth of bore hole varied from 1.60 to 12.20 at elevation of + 25,00 to – 7,20 m of sea level. Based on a series of sedimentary environment correlation, alluvial deposits can be divided into three sedimentary intervals (A,B and C). Each interval is characterized by environmental changes controlled by transgression and regression as well as climatic changes. Referring to cassiterite genesis there are three phenomena namely chemical and physical weatherings, transgression effect and climate changesKeywords: placer deposits, sediment, stratigraphy